NELSON MANDELA : Conversation with Myself - Mandela, Nelson, 1918-, author; Nelson Mandela Foundation. Nelson Mandela Centre of Memory and Dialogue (South Africa), issuing body (London: Macmillan, 2011)
Includes bibliographical references and index